Large eddy simulation: A study of clearings in forest and their effect on wind turbines. Issue 12 (23rd March 2021) - Matsfelt, Johanna; Davidson, Lars
Abstract: In this article, the Ryningsnäs site in Sweden is investigated using large eddy simulation with three different clearing setups: a homogeneous forest, that is, no clearing, the current clearing, that is, the existing clearing at the location, and an extended clearing. Neutral stratification is simulated, and the wind turbines are modelled by a two‐way‐coupled actuator line model. From the simulations, the electrical generator power was found to be the highest for the current clearing. But the fatigue loads were both higher and lower than the homogeneous forest depending on which part of the wind turbine that was investigated. The extended clearing nearly always had the lowest fatigue loads but unfortunately also the lowest electrical generator power. Further optimization of the clearings and the wind turbine locations in relation to them is needed to find the sweet spot where the fatigue loads are lower and the electrical generator power is higher.